THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMP NEGERI 4 SUKAWATI IN ACADEMIC YEAR 2021/2022 - I Putu Yoga Maha Astra; Ni Made Wersi Murtini; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2023)
The purpose of this study was to determine whether there is a substantial relationship between vocabulary knowledge and reading comprehension. of the eighth-grade students of SMP Negeri 4 Sukawati in academic year 2021/2022. Vocabulary and learning achievement, particularly reading competence, are crucial factors to consider when learning a foreign language. In the current study, there were two factors. Vocabulary was the independent variable, while reading comprehension was the dependent variable. Furthermore, the study instrument used structured sentence writing and short answer text. The research instruments were created in order to acquire the necessary data. The SPSS 23 version was used to examine the data. The data was analyzed in two steps: perquisite analysis and hypothesis testing. Pearson Product Moment Correlation and the T-test were used to assess hypotheses. The alternate hypothesis, that there was a strong association between vocabulary mastery and reading comprehension of eighth-grade students at SMP Negeri 4 Sukawati in academic year 2021/2022, was eventually accepted based on the findings of the hypothesis testing.